Oil-resistant flame-retardant anti-ultraviolet ABS (Acrylonitrile Butadiene Styrene) functional color master batch and preparation method thereof

By adding specific components to the ABS material, oil-resistant, flame-retardant, ultraviolet-resistant ABS functional masterbatch is formed, which solves the problems of degradation in ABS material's performance and poor flame-retardant performance in long-term use, and achieves the coordinated improvement of the material's oil-resistant, flame-retardant and ultraviolet-resistant properties.

CN119875291AActive Publication Date: 2025-04-25NINGBO LANGSHENG NEW MATERIAL TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510360265.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

ABS materials are susceptible to erosion by oily substances during long-term use, resulting in degradation of performance. At the same time, their flame retardant and ultraviolet resistance are poor, which limits their application in certain special environments.

Method used

It adopts an oil-resistant, flame-resistant, UV-resistant ABS functional masterbatch, whose components include ABS, PC, PET, toughener, bromotriazine, antioxidant, stabilizer, lubricant, composite UVP and composite flame retardant, and enhances oil resistance through fluorinated polymers, and composite flame retardant and composite UVP to improve flame retardant and ultraviolet resistance.

Benefits of technology

The coordinated improvement of ABS materials' oil resistance, flame retardant and ultraviolet resistance has been achieved, delaying material aging and improving its application potential in special environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875291A_ABST
    Figure CN119875291A_ABST
Patent Text Reader

Abstract

According to the oil-resistant flame-retardant anti-ultraviolet ABS functional color master batch and the preparation method thereof provided by the invention, a fluorinated polymer is adopted to meet the oil resistance of a material, a compound flame retardant is adopted to meet the flame retardance of the material, and a benzotriazole efficient ultraviolet absorbent is compounded with UVP to meet the anti-ultraviolet effect of the material. In a functional color master batch system, through the synergistic effect of the phosphorus-based flame retardant and the fluorinated polymer, the phosphorus-based flame retardant forms an expanded carbon layer during combustion, and the fluorinated polymer enhances the surface lipophobicity, so that the flame retardance and oil resistance are prevented from being reduced due to moisture absorption of the flame retardant; the benzotriazole efficient ultraviolet absorbent composite UVP and the nano cerium oxide are subjected to solid-phase grafting compounding, so that the material has excellent anti-ultraviolet performance, and the aging of the material is delayed; the interface between the added material and the resin is modified by the guanidine phosphate, so that the dispersity of functional components can be improved on the premise of not using other surface modifiers, and agglomeration is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant functional masterbatch preparation, and in particular to an oil-resistant, flame retardant and anti-ultraviolet ABS functional masterbatch and a preparation method thereof. Background Art

[0002] ABS alloy is a general term for plastic polymers obtained by modifying ABS resin to achieve certain properties. Common ABS alloys include ABS / PC, ABS / PA, ABS / PBT, ABS / PVC, etc. Among them, ABS / PC is used to improve the flame retardancy of ABS. It has good mechanical strength, toughness and flame retardancy and is used in building materials, automobile and electronics industries, such as TV sets, office automation equipment housings and telephones. In ABS / PC alloy, PC contributes heat resistance, toughness, impact strength, strength and flame retardancy. The advantages of ABS are good processability, apparent quality and low density, and its application focuses on automotive industry parts. ABS / PA is an impact-resistant, chemical-resistant material with good fluidity and heat resistance, and is used for automotive interior decoration, power tools, sports equipment, lawn mowers and snow blowers and other industrial parts, office equipment housings, etc. ABS / PBT has good heat resistance, strength, chemical resistance and fluidity, and is suitable for automotive interior decoration, motorcycle outer pads, etc. The permanent antistatic grades with antistatic agents added have the following uses: paper transfer mechanisms of copiers, fax machines, etc., IC chip supports, video and high-end audio tapes, etc.

[0003] ABS resin is widely used in the fields of automobiles, electronic appliances, building materials, etc. due to its excellent mechanical properties, processing properties and surface gloss. However, during long-term use, ABS materials are easily corroded by oil substances, resulting in performance degradation; at the same time, ABS has poor flame retardancy and UV resistance, which limits its application in some special environments. Moreover, the common ABS modification methods on the market currently mostly use functional additives such as adding flame retardants and anti-ultraviolet agents, but these methods often have problems such as uneven dispersion, easy migration of functional additives, and poor processing performance. Therefore, the development of an ABS functional masterbatch with oil resistance, flame retardancy, and UV resistance has important practical application value.

[0004] In view of this, we disclose an oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch and a preparation method thereof. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide an oil-resistant, flame-retardant and UV-resistant ABS functional masterbatch and a preparation method thereof.

[0006] To achieve the above object, the present invention proposes the following technical solutions: An oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch comprises the following raw material components in parts by weight: ABS 40-60 copies; PC 5-15 copies; PET 15-25 parts; 5-15 parts of toughening agent; 5-15 parts of bromotriazine; Antioxidant 1076 0.2-0.4 parts; Stabilizer 168 0.2-0.4 parts; Lubricant PETS 0.5-1.5 parts; Light stabilizer 770 0.3-0.5 parts; Composite UVP 0.3-0.5 parts; Compound flame retardant 0.2-0.5 parts.

[0007] Furthermore, the toughening agent is methyl acrylate-butadiene-styrene copolymer.

[0008] In the present invention, the flame retardant halogen exists in the bromotriazine, which can enhance the flame retardant property of the material; PETS (pentaerythritol stearate) is a polyol copolymer with excellent internal and external lubrication and thermal stability; UVP is an organic ultraviolet absorber 2-(2-hydroxy-5-benzyl)benzotriazole, which has excellent anti-ultraviolet effect; antioxidant 1076 is a hindered phenol antioxidant, which plays an antioxidant role for a long time by capturing free radicals generated during the degradation of plastics; stabilizer 168 belongs to the phosphite auxiliary antioxidant, which achieves the purpose of anti-oxidation by decomposing the peroxides generated by further degradation of plastics, and can also provide thermal processing stability. Composite UVP is used in conjunction with antioxidant 1076 and stabilizer 168 to provide double protection. Composite UVP absorbs ultraviolet rays and prevents polymers from degrading due to absorption of ultraviolet energy. Nano cerium oxide in the composite UVP combination has ultraviolet absorption, and UVP can capture free radicals by using its structure, thereby forming a "ultraviolet absorption-free radical capture" dual protection mechanism to delay material aging.

[0009] Furthermore, the composite UVP is a solid phase grafted composite product of nano-cerium oxide and UVP, and the mass ratio of nano-cerium oxide to UVP is (1.1-1.3): 1. Specifically, nano-cerium oxide and UVP are placed in an internal mixer at 120° C. and a rotor speed of 90 rpm for shear mixing for 35-60 minutes, and the obtained block mixture is then ground using a planetary ball mill to obtain a composite powder, and finally an isooctane / toluene PCB28 standard solution is used at 50-60° C. to remove UVP that does not participate in the reaction in the composite powder, and finally dried to obtain the target product composite UVP.

[0010] Furthermore, the composite flame retardant includes a fluorinated polymer, ammonium polyphosphate and guanidine phosphate, and the mass ratio of the three is (3.5-4.5):(1.8-2.6):1.

[0011] Furthermore, the fluorinated polymer is polyvinylidene fluoride or polytetrafluoroethylene powder. The fluorinated polymer can enhance the surface oleophobicity and improve the oil resistance of the material; and the material has a synergistic flame retardant effect with the phosphorus-nitrogen series of ammonium polyphosphate and guanidine phosphate in the compound flame retardant, and the fluorinated polymer can avoid the flame retardancy degradation and failure caused by moisture absorption of the flame retardant system.

[0012] Furthermore, the guanidine phosphate in the compound flame retardant is synthesized by reacting polyphosphoric acid and guanidine carbonate as raw materials, including two processes: preparation of anhydrous phosphoric acid and material kneading, mixing and decarbonization.

[0013] Furthermore, the following raw materials are included by weight: ABS 50 copies; PC 10 copies; PET 20 parts; 10 parts of toughening agent; 10 parts of bromotriazine; Antioxidant 1076 0.3 parts; Stabilizer 168 0.3 parts; Lubricant PETS 1.0 part; Composite UVP 0.3 parts; Light stabilizer 770 0.4 parts; 0.3 parts of compound flame retardant.

[0014] Furthermore, a method for preparing an oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch comprises the following steps: S1. Material pretreatment and preparation: Toughener, bromotriazine, antioxidant 1076, stabilizer 168, lubricant PETS, composite UVP, light stabilizer 770 powder, and compound flame retardant were used as auxiliary materials for drying and activation treatment, and ABS resin, PC, and PET pellets were placed in a dryer as base materials for dry frying; S2. Material mixing: The base material and auxiliary materials are placed in a mixer according to proportion and mixed evenly to obtain a mixture; S3, extrusion granulation: The mixed material is placed in the storage tank of the twin-screw extruder, and then goes through the hopper and the feeding port to the twin-screw main machine. Finally, the material passes through the screen changing device and the die, and is shaped by pulling through the cooling water tank, and then passes through the air dryer and pelletizer to obtain the functional masterbatch, and finally goes to the storage box for material storage of the functional masterbatch; S4. Dry packaging: The above S3 functional masterbatch is dried in a dryer, and the materials are mixed in a mixing tank according to the use requirements. After packaging and measurement, they are inspected and sealed, and finally put into storage.

[0015] Furthermore, the temperature of each temperature control zone of the twin-screw extruder in step S3 is: Zone 1: 175-185℃, Zone 2: 195-205℃, Zone 3: 220-230℃, Zone 4: 230-240℃, Zone 5: 250-260℃, Zone 6: 250-260℃, Zone 7: 250-260℃, Zone 8: 250-260℃, machine head: 240-250℃, feeding speed: 9-15rpm, main engine speed: 25-35 rpm.

[0016] Furthermore, the drying temperature of step S4 is 80-105° C., and the drying time is 2-4 hours.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention discloses an oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch, which uses a fluorinated polymer to meet the material's oil resistance, a compounded flame retardant to meet the material's flame retardancy, and a benzotriazole-based high-efficiency UV absorber compounded with UVP to meet the material's UV resistance. The functional masterbatch system of the present invention also has the following advantages: 1. Collaborative design of flame retardancy and oil resistance: Through the synergistic effect of phosphorus flame retardants and fluorinated polymers, the phosphorus flame retardants form an expanded carbon layer when burned, and the fluorinated polymers enhance the surface oleophobicity, avoiding the decrease in flame retardancy and oil resistance caused by moisture absorption by the flame retardant.

[0018] 2. Anti-ultraviolet stabilization system: Benzotriazole ultraviolet absorber UVP is solid-phase grafted and compounded with nano-cerium oxide to form a dual protection mechanism of "ultraviolet absorption-free radical capture", which can delay material aging.

[0019] 3. Dispersion optimization: By modifying the interface between the additive and the resin through guanidine phosphate, the dispersion of the functional components can be improved and agglomeration can be avoided without using other surface modifiers.

[0020] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered part of the present subject matter disclosure to the extent such concepts are not mutually inconsistent.

[0021] The foregoing and other aspects, embodiments and features of the present invention will be more fully understood from the following description. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or will be learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 It is a preparation process flow chart of the present invention. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific examples, but it should not be understood as a limitation of this patent.

[0024] The experimental methods or test methods described in the following examples / comparative examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0025] Among them, the composite UVP is to place cerium oxide and UVP powder in a vacuum oven at 80°C and dry for 24 hours to remove moisture, and then weigh and mix them evenly according to a certain mass ratio. At 120°C and a rotor speed of 90rpm, the mixed powder is added to the internal mixer for high-speed shear mixing for 35-60min. The product obtained by mixing is in block form. In order to ensure that the sample can be used as an additive, a planetary ball mill is used to grind the block mixture at a speed of 300rpm to obtain a composite product after the reaction of nano-cerium oxide and UVP, which is light yellow. In order to consume UVP as much as possible to participate in the reaction, the proportion of nano-cerium oxide used will be higher than that of UVP, but it cannot exceed the practical amount, because although excessive nano-cerium oxide consumes UVP completely, excessive nano-cerium oxide is prone to agglomeration, which affects the function of composite UVP. Preferably, in order to remove the unreacted UVP in the mixed powder as much as possible, the mixed powder is washed 2-3 times with isooctane / toluene PCB28 standard solution, and the washing conditions are: 50-60℃ magnetic stirring dissolution for 0.5-1h, and finally dried at 60℃ for at least 10h to obtain a grafted composite product, i.e., composite UVP. Moreover, the product washed with the standard solution has better interface bonding and is more compatible with the base material. The molecular formula of the UVP of the present invention is C 13 H 11 N 3 O, light yellow-green powder, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0026] Furthermore, the guanidine phosphate in the composite flame retardant of the present invention is synthesized by reacting polyphosphoric acid and guanidine carbonate as raw materials, including two processes of preparing anhydrous phosphoric acid and kneading and mixing the materials to remove carbon. The preparation method is as follows: Weigh the raw materials according to the molar ratio of polyphosphoric acid to guanidine carbonate (2-3):1. First, put the weighed polyphosphoric acid into the kneader. When the temperature of the polyphosphoric acid rises to 78°C, add a certain amount of water to the kneader, stir and react for about 2 hours, and then heat it to 100°C. This process is the preparation of anhydrous phosphoric acid. The fluidity of polyphosphoric acid will increase with the increase of temperature, showing a positive correlation trend, and the decomposition rate will also increase; but the decomposition of polyphosphoric acid is an exothermic reaction. If guanidine carbonate is added to the system later, the reaction will continue to release heat, which will increase the uncontrollability of the reaction and produce a large amount of gas. Therefore, in order to better control the reaction, the first temperature of polyphosphoric acid is set below 85°C. After testing, under the condition of a molar ratio of (2-3):1, the first temperature rise of polyphosphoric acid is selected to be 78°C.

[0027] Further, it is the process of material kneading and mixing to remove carbon. The weighed guanidine carbonate is slowly added to the kneader through a screw feeder, the reaction process is observed, the feed rate is appropriately adjusted, and the frequency of the kneader stirring motor is adjusted to 50Hz. This frequency can ensure sufficient stirring and prevent the generated guanidine phosphate from wrapping the unreacted guanidine carbonate. After stirring and reacting for 1.5-2.5h, the temperature rises to 120℃, and the frequency of the kneader stirring motor is adjusted to 25Hz. This stage is the evaporation and drying stage. The whole system is a soft solid with greater resistance. Observe the reaction process. When there is no obvious liquid on the inner wall of the kneader and the material is wet, in order to protect the machine and equipment, adjust the frequency of the kneader stirring motor to 10Hz, continue stirring and evaporating and dehydrating for 1h, until the product is dried to a white powder, and obtain the guanidine phosphate product. Turn the cylinder to discharge the material, and obtain guanidine phosphate. Among them, polyphosphoric acid and guanidine carbonate were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0028] Ammonium polyphosphate and guanidine phosphate are used in combination, and ammonium polyphosphate is used as a halogen-free flame retardant; guanidine phosphate can enhance the interaction between different materials, making it more evenly dispersed in the matrix resin, thereby more effectively improving the mechanical properties of the blend, so that when the resin is not modified with a coupling agent, the compound flame retardant can also improve the interfacial bonding performance between the matrix material and the additive. Moreover, the combination of ammonium polyphosphate and guanidine phosphate is a phosphorus-based flame retardant. When the functional masterbatch is subjected to a high-temperature fire source, in addition to its own elemental flame retardant properties, it can also act as an acid source and a gas source; coupled with the fluorinated polymer in the compound flame retardant, the entire flame retardant forms a FP flame retardant system, which plays a dual flame retardant role.

[0029] Performance Testing In order to better conduct performance testing, we used an injection molding machine to inject the functional masterbatch into a standard specimen with a thickness of 2 mm to obtain an ABS functional alloy plate, and then conducted further testing according to the performance test standards.

[0030] Mechanical properties test Mechanical properties tests include tensile strength, flexural modulus, and notched impact strength. The tensile strength and flexural modulus are tested in accordance with GB / T 1040.2-2006. According to relevant test requirements and regulations, the sample size is uniformly controlled to 185 mm×20 mm×2 mm; further, the test speed in the tensile strength test is 50 mm / min. The notched impact strength is tested in accordance with GB / T 1843-2008. According to relevant test requirements and regulations, the sample size is 80 mm×10 mm×2 mm.

[0031] Oil resistance test The oil resistance of a 2mm thick standard sample was tested. According to the ASTMD 471 test standard, the sample was placed at 100°C and immersed for 36 hours. After the immersion, the sample was taken out and the surface oil was removed. The thickness of the sample was tested with a vernier caliper. The volume expansion was determined based on the change in the sample thickness, and then whether it was oil resistant was determined.

[0032] Flame retardant properties A flame retardant test was conducted on a standard sample with a thickness of 2 mm. Specifically, the 60 s vertical burning test was conducted in accordance with HB 5469. The size of the vertical burning sample was 368 mm × 76 mm × 2 mm.

[0033] UV resistance The UV resistance of the sample is also an important indicator. Taking into account the influence of the transmittance of too thick samples, the UV resistance of the material is controlled by controlling the sample thickness to 0.3 mm and the sample size to 50 mm × 50 mm × 0.3 mm. Then a spectrometer is used to measure the UV transmittance in different bands.

[0034] Examples 1-3 An oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch is prepared by weighing the components shown in Table 1 by weight percentage: a toughener, bromotriazine, an antioxidant 1076, a stabilizer 168, a lubricant PETS, a composite UVP, a light stabilizer 770 powder, a compound flame retardant and other auxiliary materials, and base materials such as ABS resin, PC, and PET. The materials of Examples 1 to 3 are weighed according to the formula in the table.

[0035] Furthermore, the base material is placed in a dryer for dry frying, the auxiliary materials are dried and activated, and then the materials prepared according to the ratio are evenly mixed in a mixer to obtain a mixture. Furthermore, the mixture is placed in a twin-screw extruder storage tank, and then passed through a hopper and a feeding port to a twin-screw main machine. Finally, the material passes through a screen changing device and a machine head, and is shaped by pulling through a cooling water tank, and then passes through an air dryer and a pelletizer to obtain a functional masterbatch, and finally goes to a storage box for material storage of the functional masterbatch; the functional masterbatch is then dried in a dryer, and the materials are mixed in a mixing tank according to the use requirements, and then packaged, measured, inspected, and packaged, and finally put into storage.

[0036] The temperature of each temperature control zone of the twin-screw extruder is: Zone 1: 175-185℃, Zone 2: 195-205℃, Zone 3: 220-230℃, Zone 4: 230-240℃, Zone 5: 250-260℃, Zone 6: 250-260℃, Zone 7: 250-260℃, Zone 8: 250-260℃, machine head: 240-250℃, feeding speed: 9-15rpm, main engine speed: 25-35 rpm.

[0037] The extruded resin pellets are dried at 80-105°C for 2-4 hours, then packaged, weighed, inspected, and packaged.

[0038] Comparative Example 1 The difference from Example 1 is that the composite UVP uses UVP of the same brand and quality, and the rest is the same as Example 1.

[0039] Comparative Example 2 The difference from Example 1 is that the composite UVP uses the same grade and quality of nano-cerium oxide, and the rest is the same as Example 1.

[0040] Comparative Examples 3-7 Different from Example 1, base materials such as ABS resin, PC, and PET, toughening agent, bromotriazine, antioxidant 1076, stabilizer 168, lubricant PETS, composite UVP, light stabilizer 770 powder, compound flame retardant and other auxiliary materials are weighed according to the proportions shown in Table 1. After the base material is placed in a dryer for dry frying, and the auxiliary materials are dried and activated, the materials prepared according to the ratio are uniformly mixed in a mixer to obtain a mixture. The mixture is then melt-blended and extruded through a twin-screw extruder, towed, granulated, and dried to prepare ABS functional masterbatch.

[0041] The other process steps not specifically described are prepared by referring to Examples 1-3.

[0042] Table 1 Material formula

[0043] According to different test standards, relevant performance test analysis was performed on Examples 1-3 and Comparative Examples 1-7. The relevant test comparison results are shown in Table 2.

[0044] Table 2 Test results comparison analysis table

[0045] From the comparative results of Table 1-Table 2 above, it can be seen that the ABS alloy plastic masterbatch of the present invention has the characteristics of oil resistance, UV resistance and good flame retardant effect. From Test Table 2, the ABS alloy plastic masterbatch prepared in Comparative Examples 1-3 has poor barrier properties in the long-wave ultraviolet band and a short wavelength absorption range; and the UVP element has a greater impact on the UV resistance of the material. In addition, according to the molecular structure of the compound, the benzotriazole ultraviolet absorber UVP and nano-cerium oxide are solid-phase grafted and compounded to form a "ultraviolet absorption-free radical capture" dual protection mechanism, which can delay material aging. Moreover, the single substance UVP or nano-cerium oxide has the problem of filler agglomeration affecting the interface compatibility in the base material, which in turn affects the mechanical properties of the ABS alloy sheet. In Comparative Example 3, the lack of composite UVP also has a certain impact on the flame retardant effect. The presence of N element in the molecular structure of UVP can also provide flame retardant elements in the event of fire or combustion.

[0046] The lack of fluorinated polymer in Comparative Example 4 will affect the oil resistance of the masterbatch, and the oleophobicity of the surface of the fluorinated polymer will also affect the flame retardancy of the material as a whole, thereby destroying the flame retardant synergy between the fluorinated polymer and the phosphorus flame retardant. From the test results of the samples prepared in Comparative Examples 4 to 7, it can be seen that although the guanidine phosphate in the composite flame retardant has no greater effect on the flame retardancy of the material than the other two composite materials, the lack of the introduction of guanidine phosphate affects the mechanical properties of the material, and the combination of the three has a relatively large effect on the flame retardancy of the composite material.

[0047] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. An oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch, characterized in that: The composition includes the following raw materials by weight: ABS 40-60 copies; PC 5-15 copies; PET 15-25 parts; 5-15 parts of toughening agent; 5-15 parts of bromotriazine; Antioxidant 1076 0.2-0.4 parts; Stabilizer 168 0.2-0.4 parts; Lubricant PETS 0.5-1.5 parts; Light stabilizer 770 0.3-0.5 parts; Composite UVP 0.2-0.5 parts; Compound flame retardant 0.2-0.5 parts.

2. The oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 1, characterized in that: The toughening agent is methyl acrylate-butadiene-styrene copolymer.

3. The oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 1, characterized in that: The composite UVP is a mixture of nano-cerium oxide and UVP, and the mass ratio of nano-cerium oxide to UVP is (1.0-1.6):

1.

4. The oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 1, characterized in that: The composite flame retardant comprises a fluorinated polymer, ammonium polyphosphate and guanidine phosphate, and the mass ratio of the three is (3.5-4.5):(1.8-2.6):

1.

5. The oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 4, characterized in that: The fluorinated polymer is polyvinylidene fluoride or polytetrafluoroethylene powder.

6. The oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 1, characterized in that: The composition includes the following raw materials by weight: ABS 50 copies; PC 10 copies; PET 20 parts; 10 parts of toughening agent; 10 parts of bromotriazine; Antioxidant 1076 0.3 parts; Stabilizer 168 0.3 parts; Lubricant PETS 1.0 part; Light stabilizer 770 0.4 parts; Composite UVP 0.3 parts; 0.3 parts of compound flame retardant.

7. A method for preparing the oil-resistant, flame-retardant and UV-resistant ABS functional masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Material pretreatment and preparation: Toughener, bromotriazine, antioxidant 1076, stabilizer 168, lubricant PETS, composite UVP, light stabilizer 770 powder, and compound flame retardant were used as auxiliary materials for drying and activation treatment, and ABS resin, PC, and PET pellets were placed in a dryer as base materials for dry frying; S2. Material mixing: The base material and auxiliary materials are placed in a mixer according to proportion and mixed evenly to obtain a mixture; The above materials are placed in a mixer according to proportion and mixed evenly to obtain a mixture; S3, extrusion granulation: The mixed material is placed in the storage tank of the twin-screw extruder, and then goes through the hopper and the feeding port to the twin-screw main machine. Finally, the material passes through the screen changing device and the die, and is shaped by pulling through the cooling water tank, and then passes through the air dryer and pelletizer to obtain the functional masterbatch, and finally goes to the storage box for material storage of the functional masterbatch; S4. Dry packaging: The functional masterbatch in step S3 is dried in a dryer, and the materials are mixed in a mixing tank according to the use requirements, and then packaged, measured, inspected, and packaged, and finally stored.

8. The method for preparing an oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 7, characterized in that: The temperature of each temperature control zone of the twin-screw extruder in step S3 is: Zone 1: 175-185℃, Zone 2: 195-205℃, Zone 3: 220-230℃, Zone 4: 230-240℃, Zone 5: 250-260℃, Zone 6: 250-260℃, Zone 7: 250-260℃, Zone 8: 250-260℃, machine head: 240-250℃, feeding speed: 9-15 rpm, main engine speed: 25-35 rpm.

9. The method for preparing an oil-resistant, flame-retardant, and UV-resistant ABS functional masterbatch according to claim 7, characterized in that: The drying temperature of step S4 is 80-105° C., and the drying time is 2-4 hours.

Citation Information

Patent Citations

  • Low temperature resistant environment-friendly inflaming retarding PC / PET alloy and method for preparing same

    CN101712793A

  • PVC high weather-resistant rain water pipe

    CN106589704A

  • Anti-ultraviolet halogen-free flame-retardant PC / ABS (polycarbonate / acrylonitrile butadiene styrene) alloy and method for preparing same

    CN108148391A

  • Environment-friendly high flame retardant and light-heat aging resistant halogen-free polypropylene material capable of meeting UL94-5VA and preparation method of polypropylene material

    CN108250572A

  • ABS / PET / PC (Acrylonitrile Butadiene Styrene / Polyethylene terephthalate / Polycarbonate) composite material for automobile bumper and preparation method of material

    CN109486088A